1994
DOI: 10.1172/jci117555
|View full text |Cite
|
Sign up to set email alerts
|

Severe microcephaly induced by blockade of vasoactive intestinal peptide function in the primitive neuroepithelium of the mouse.

Abstract: Vasoactive intestinal peptide (VIP) has potent growth-related actions that influence cell mitosis, neuronal survival, and neurodifferentiation in cell culture. VIP can also produce dramatic growth in postimplantation mouse embryos in vitro, characterized by large increases in cell number. The goal of the present study was to assess the role of VIP on early nervous system development in vivo. Pregnant mice were treated with a specific antagonist to VIP. Prenatal administration of the antagonist early in develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 36 publications
4
77
1
Order By: Relevance
“…Although binding experiments revealed that PAC1 receptors are predominant, the VPAC1 receptor has been shown to be slightly expressed by granule neurons in vitro [16]. While it is possible that VIP, which increases granule cell survival in mice [5] and exhibits neurotrophic activities during development [8], may at least in part compensate for the lack of PACAP, this seems unlikely here, since we were unable to detect any compensatory increase in VIP mRNA in cerebella of PACAP-deficient, compared to wild type mice. The fact that PACAP-deficient neurons are more sensitive to neurotoxic insult suggests that PACAP mainly acts as an emergency response peptide supporting neuronal survival under sustained pathophysiological conditions, which might suggest some useful applications for PACAP-like ligands in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although binding experiments revealed that PAC1 receptors are predominant, the VPAC1 receptor has been shown to be slightly expressed by granule neurons in vitro [16]. While it is possible that VIP, which increases granule cell survival in mice [5] and exhibits neurotrophic activities during development [8], may at least in part compensate for the lack of PACAP, this seems unlikely here, since we were unable to detect any compensatory increase in VIP mRNA in cerebella of PACAP-deficient, compared to wild type mice. The fact that PACAP-deficient neurons are more sensitive to neurotoxic insult suggests that PACAP mainly acts as an emergency response peptide supporting neuronal survival under sustained pathophysiological conditions, which might suggest some useful applications for PACAP-like ligands in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mouse embryos in culture and in utero suggest that VIP stimulates proliferation and survival during neurogenesis, an activity not shared by PACAP (29,30). Furthermore, although VIP is apparently derived from the mother (31) and acts through cAMP-independent pathways (29), PACAP is expressed by cortical precursors in vitro and in vivo (10) and acts via PACAP type I receptors and the cAMP cascade, supporting peptide-specific functions.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant Swiss mice were injected intraperitoneally twice a day (8-9 am and 6-7 pm) between E9.5 and E11.5 with 50 μl of either PBS (vehicle) or VA (hybrid of VIP and neurotensin, which is a competitive antagonist of VIP receptors (83), or again VIP, according to the original protocol designed by Gressens et al (43,44). Both peptides were purchased from Bachem and injected at the final concentration of 2 μg/g body weight.…”
Section: Methodsmentioning
confidence: 99%
“…In line with these data, in the early 1990s, Gressens and coworkers described a pharmacologically induced murine model of microcephaly (44). In the latter, maternal VIP was challenged by a wellcharacterized VIP antagonist (VA) (45)(46)(47), which, when injected into pregnant females during neurogenesis (E9-E11), led to cortical alterations of newborn pups.…”
Section: Introductionmentioning
confidence: 98%